Kompetensi Guru Dalam Perspektif Pendidikan Agama Kristen - Marthen Lengkong (THEOSOPHIA: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Abstract: Christian Religious Education (CRE) teacher competency is the ability, ability and expertise both in technical and behavioral terms of a teacher who professionally educates, teaches, guides, directs, trains, assesses and evaluates students to build Christian beliefs after receiving the teaching, students enter a living communion of faith with God. Religious Education teachers have at least two roles that must be carried out in relation to their profession. The first is the role as a teacher in general in carrying out responsibilities in schools or educational institutions; the second is the role in terms of faith responsibility in bringing students to know the Creator and the work of salvation as well as correct life guidelines. In general, teacher competence includes pedagogical competence, personality competence, professional competence and social competence. The competence of CRE teachers cannot be found directly in the Bible. However, this does not mean that the Bible never speaks about the competence of CRE teachers. In the Old Testament (OT), education began when God created humans where God positioned Himself as a teacher or teacher in the process of teaching humans about His laws and regulations. In the New Testament (NT), the central figure is Jesus the Great Teacher. All teacher competence rests with Him. In the CRE perspective, teacher competency is something that is very relevant and has a direct connection because the principles applied are in line and complement each other so that CRE teachers are also required to have these competencies. Abstrak: Kompetensi guru Pendidikan Agama Kristen (PAK) adalah kemampuan, kesanggupan dan keahlian baik dalam hal teknis maupun perilaku seorang guru yang secara profesional mendidik, mengajar,  membimbing, mengarahkan,  melatih,  menilai,  dan  mengevaluasi  peserta  didik  untuk membangun kepercayaan Kristen dimana setelah menerima pengajaran itu, peserta didik memasuki persekutuan iman yang hidup dengan Tuhan. Guru PAK memiliki setidaknya dua peran yang harus dilakukan dalam hubungan dengan profesinya. Pertama adalah peran sebagai guru secara umum dalam melaksanakan tanggung jawab di sekolah atau lembaga pendidikan; yang kedua adalah peran dalam hal tanggung jawab iman dalam membawa peserta didik untuk mengenal Pencipta dan karya keselamatan serta pedoman hidup yang benar. Secara umum, kompetensi guru meliputi kompetensi pedagogis, kompetensi kepribadian, kompetensi profesional dan kompetensi sosial. Kompetensi guru PAK tidak dapat ditemukan langsung dalam Alkitab. Namun demikian bukan berarti bahwa Alkitab tidak pernah berbicara mengenai kompetensi guru PAK. Dalam Perjanjian Lama (PL), pendidikan dimulai sejak Allah menciptakan manusia di mana Allah memposisikan diri-Nya sebagai pengajar atau guru dalam proses mengajar manusia tentang hukum-hukum dan peraturan-Nya. Dalam Perjanjian Baru (PB), tokoh sentralnya adalah Yesus sang Guru Agung. Semua kompetensi guru ada pada-Nya. Dalam perspektif PAK, kompetensi guru merupakan hal yang sngat relevan dan beririsan langsung karena  prinsip-prinsip  yang  diterapkan  sejalan  dan  saling melengkapi  segingga  guru  PAK juga diharuskan untuk memiliki kompetensi-kompetensi tersebut.